Analysing inflation dynamics in the Philippines using the new Keynesian Phililips curve. - Cacnio, Faith Christian Q. (2013)
This study analyses short-run inflation dynamics in the Philippines using the new Keynesian Phillips curve (NKPC) framework. The NKPC highlights the inclusion of microbased behavioral models for economic agents (i.e., households and firms) in deriving the relationship between inflation and economic activity. A key finding of this paper is the declining sensitivity of inflation to changes in the real variables of the economy. Various reasons have been cited to explain this phenomenon, which is often referred to in the literature as the flattening of the Phillips curve. For the Philippines, the adoption of inflation targeting and increased trade openness contributed to the flattening of the Phillips curve.
Keywords: Phillip's curve; Inflation (Finance)